Prolonged withdrawal from cocaine self-administration affects prefrontal cortex- and basolateral amygdala-nucleus accumbens core circuits but not accumbens GABAergic local interneurons - Purgianto, Anthony (Addict Biol, 2016)
Withdrawal from extended-access cocaine self-administration leads to progressive intensification (‘incubation’) of cocaine craving. After prolonged withdrawal (1–2 months), when craving is high, expression of incubation depends on strengthening of excitatory inputs to medium spiny neurons (MSN) of the nucleus accumbens (NAc). These excitatory inputs interact with the intra-NAc GABAergic ‘microcircuit’, composed of MSN axon collaterals and GABAergic interneurons. Here, we investigated whether the increased glutamatergic neurotransmission observed after prolonged withdrawal is accompanied by altered GABAergic neurotransmission, focusing on NAc core. Rats self-administered cocaine or saline (6 h/day) and then underwent >40 days of withdrawal. First, we investigated parvalbumin positive (PV+) interneurons, GABAergic fast-spiking interneurons that regulate MSN activity. Immunohistochemical studies revealed no significant change in PV signal intensity or the number of PV+ cells in cocaine rats versus saline controls. We then screened PV and other interneuron markers using immunoblotting. We detected no changes in levels of PV, calretinin, calbindin, or neuronal nitric oxide synthase. Since expression of these markers is activity-dependent, our results suggest no marked changes in interneuron activity. Finally, we utilized local field potential recording, which can detect GABA-mediated alterations at the circuit level, to investigate potential changes in two circuits implicated in cocaine craving: prelimbic prefrontal cortex to NAc core and basolateral amygdala to NAc core. We detected differential adaptations in these circuits, some of which may involve GABA. Overall, our results suggest that alterations in GABA transmission may accompany incubation of cocaine craving, but they are circuit-specific and less pronounced than alterations in glutamate transmission.